Cobalt(II) Complexes of 4′–Nitro–Fenamic Acid: Characterization and Biological Evaluation - Georgios Malis; Antigoni Roussa; Efstathia Aikaterini Papantopoulou; Stavros Kalogiannis; Antonios G. Hatzidimitriou; Konstantina C. Fylaktakidou; George Psomas (Molecules)
A nitro-derivative of fenamic acid (4′–nitro–fenamic acid) was synthesized and used as ligand for the synthesis of four Co(II) complexes in the absence or presence of the N,N′-donors 2,2′–bipyridylamine, 1,10–phenanthroline and 2,9–dimethyl–1,10–phenanthroline. The characterization of the resultant complexes was performed with diverse techniques (elemental analysis, molar conductivity measurements, IR and UV-vis spectroscopy, single-crystal X-ray crystallography). The biological evaluation of the compounds encompassed (i) antioxidant activity via hydrogen peroxide (H2O2) reduction and free radical scavenging; (ii) antimicrobial screening against two Gram-positive and two Gram-negative bacterial strains; (iii) interactions with calf-thymus (CT) DNA; (iv) cleavage of supercoiled pBR322 plasmid DNA (pDNA), in the dark or under UVA/UVB/visible light irradiation; and (v) binding affinity towards bovine and human serum albumins. The antioxidant activity of the compounds against 2,2′–azinobis–(3–ethylbenzothiazoline–6–sulfonic acid) radicals and H2O2 is significant, especially in the case of H2O2. The complexes exhibit adequate antimicrobial activity against the strains tested. The complexes interact with CT DNA through intercalation with binding constants reaching a magnitude of 106 M−1. The compounds have a significantly enhanced pDNA-cleavage ability under irradiation, showing promising potential as photodynamic therapeutic agents. All compounds can bind tightly and reversibly to both albumins tested.